Leakage effects due to bristle deflection and wear in hybrid brush seal of high-pressure steam turbine - Ha, Yunseok; Ha, Taewoong; Byun, Jaeseung; Lee, Yongbok (ELSEVIER SCI LTD, 2020)
This study investigated the effect of clearance between a rotor and hybrid brush seal for leakage flow in terms of the axial deflection and wear. The leakage flow was experimentally measured according to pressure difference, and the Darcian porous medium-based CFD model was used to predict leakage flow according to clearance and rotational speed. The bristle's axial deflection was estimated according to the external force, the brush seal compliance was derived based on the cantilever beam theory, and the bristle wear and oxidation under super-heated steam and high-speed operation environments were studied. The accuracy of the CFD model that considered the clearance change was improved by 11% compared to that of the previous CFD model.
Keywords: FLOW-FIELDS; GEOMETRY; MODEL